The Role of the Notary in the Credit Agreement with Mortgage Guarantee (Case Study in the Bank Tabungan Negara (Persero) Tbk) - Amalia Chusna Chusna; Jawade Hafidz (Jurnal Akta, 2019)
The purpose of this study was to: 1) Analyze determine and analyze the role of the notary in the completion of the loan agreement with collateral Mortgage PT. Bank Tabungan Negara (Persero) Tbk. 2). Analyzing the causes of a default in settlement of loans with collateral Mortgage PT. Bank Tabungan Negara (Persero) Tbk. 3) Analyze the settlement of disputes in the credit agreement with collateral Mortgage PT. Bank Tabungan Negara (Persero) Tbk.This research is a field research or empirical research with sociological juridical approach. Sociolegal research done by researching in the field (field research) by means of interviews with respondents who are the primary data and researching library materials is a secondary data and also referred to the research literature. Analysis of data using Qualitative analysis.The research results are: 1) Task, responsibilities and authority of the Notary is a deed of credit agreement requested by the bank based on information that is clear, to legalize the deed of credit agreement, and is responsible for the correctness, accuracy, completeness of documents, provide counseling to clients / debtors , conceal the identity of the debtor's creditors, enter into a deed of the District Court registry book. 2) Notarial acts as a public official entitled to a deed of credit agreement. And provide legal certainty for the parties to the credit agreement. Besides the role of the Notary as well as the authorities to check against collateral in the form of Encumbrance to ascertain whether goods such guarantee was legal or not, or to avoid if there is a possibility in the collateral Mortgage were made in the warranty is still disputed law or case law. 3) Barriers faced by a Notary is a lack of understanding on banking borrowers, thus providing an explanation to the parties concerned to a mistake in making the agreement can be minimized.Keywords: Deed; Loan Agreement; Encumbrance.